2013
DOI: 10.1021/np400433g
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthesis of Mallotus B from Rottlerin: Evaluation of Cytotoxicity and Apoptosis-Inducing Activity

Abstract: Mallotus B (2d) is a prenylated dimeric phloroglucinol compound isolated from Mallotus philippensis. There have been no reports on the synthesis or biological activity of this compound. In the present paper, a semisynthetic preparation of mallotus B is reported via base-mediated intramolecular rearrangement of rottlerin (1), which is one of the major constituents of M. philippensis. The homodimer "rottlerone" was also formed as one of the products of this base-mediated intramolecular reaction. Rottlerin (1), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The cell cycle arrest has become an appreciated target for management and treatment of tumor cells with cytotoxic agents [ 46 ]. The fluorescence intensity of sub G 0 cell fraction represents the apoptotic cell population [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cell cycle arrest has become an appreciated target for management and treatment of tumor cells with cytotoxic agents [ 46 ]. The fluorescence intensity of sub G 0 cell fraction represents the apoptotic cell population [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies identified that rottlerin is an inhibitor of PKCδ (protein kinase C δ) [8]. In recent years, increasing evidence implicated that rottlerin exhibited its anti-tumor activity through inhibition of cell proliferation [9] and migration [10], induction of apoptosis [11] and cell cycle arrest [12] in a variety of human cancer cells. Interestingly, rottlerin was discovered to induce autophagy and apoptotic cell death through PKCδ-independent pathway [13].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we found that desmethylxanthohumol inhibits α-glucosidase in vitro [8]. Furthermore, our recent investigations revealed that dehydrocyclodesmethylxanthohumol (2) and its dimer analogue rottlerone (3) [9] exhibited more potent α-glucosidase inhibitory activity than 1 (Figure 1). Therefore, we prepared a series of rottlerone derivatives 4a-d and 5a-d for the purpose of studying structure-activity relationships and improving the α-glucosidase inhibitory potencies of compounds 1-3.…”
Section: Introductionmentioning
confidence: 92%
“…13 C NMR (100 MHz, d 6 -DMSO) 203.0, 165.3, 160.4, 157.0, 125.2, 116.7, 105.1, 102.3, 95.8, 78.3, 33.3, 27.8.3.1.4. 1,1'-(Methylenebis(5,7-dihydroxy-2,2-dimethyl-2H-chromene-6,8-diyl))bis (ethan-1-one)(9) Compound 8 (1.0 mmol) in CH 2 Cl 2 (10 mL) was added polyformaldehyde (0.5 mmol) and refluxed for 8 h. Solvent was removed under reduced pressure and the residue was purified by column chromatography on silica (petroleum ether/ethyl acetate 200:1) to afford a compound 9 (170 mg, 71%) as a yellow solid.1 H NMR (400 MHz, CDCl 3 ) 15.81 (s, 2H), 9.43(s, 2H), 6.63 (d, J = 10.0 Hz, 2H), 5.43 (d, J = 10.0 Hz, 2H), 3.75 (s, 2H), 2.67 (s, 6H), 1.47 (s, 12H). 13 C NMR (100 MHz, CDCl 3 ) 202.8, 160.2, 157.3, 154.9, 124.0, 116.0, 104.9, 104.0, 102.4, 77.1, 31.7, 26.9, 14.4.…”
mentioning
confidence: 99%